efectuati (x-3)(x+3)(x^2+9)(x^4+81)
Răspunsuri la întrebare
Răspuns de
2
(x+y)(x-y)=x²-y²
=(x²-9)(x²+9)(x⁴+81)=(x⁴-81)(x⁴+81)=x^8-81²=x^8-6561
=(x²-9)(x²+9)(x⁴+81)=(x⁴-81)(x⁴+81)=x^8-81²=x^8-6561
Răspuns de
0
(x-3)(x+3)(x^2+9)(x^4+81)
=(x^2-9)(x^2+9)(x^4+81)
=(x^2)^2-81)(x^4+81)
=(x^4-81)(x^4+81)
=(x^4)^2-81^2
=x^8-6561
Sper sa te ajute :)
=(x^2-9)(x^2+9)(x^4+81)
=(x^2)^2-81)(x^4+81)
=(x^4-81)(x^4+81)
=(x^4)^2-81^2
=x^8-6561
Sper sa te ajute :)
Alte întrebări interesante
Geografie,
8 ani în urmă
Engleza,
8 ani în urmă
Limba română,
8 ani în urmă
Engleza,
9 ani în urmă
Geografie,
9 ani în urmă
Matematică,
9 ani în urmă